2007
DOI: 10.1038/nn1839
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Ca2+ buffers control the strength of a fast post-tetanic hyperpolarization mediated by the α3 Na+/K+-ATPase

Abstract: The excitability of CNS presynaptic terminals after a tetanic burst of action potentials is important for synaptic plasticity. The mechanisms that regulate excitability, however, are not well understood. Using direct recordings from the rat calyx of Held terminal, we found that a fast Na(+)/K(+)-ATPase (NKA)-mediated post-tetanic hyperpolarization (PTH) controls the probability and precision of subsequent firing. Notably, increasing the concentration of internal Ca(2+) buffers or decreasing Ca(2+) influx led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 48 publications
9
90
0
Order By: Relevance
“…Among different NAKα subunits, only NAKα3 is present in the presynaptic side of neurons (27,(46)(47)(48). Electrophysiological studies have also shown the importance of NAKα3 in the presynaptic function (49,50). Our data are consistent with ASPD binding to presynaptic NAKα3 of mature neurons, leading to activation of presynaptic N-type VGCC, and eventual death of NAKα3-expressing neurons.…”
Section: Discussionsupporting
confidence: 86%
“…Among different NAKα subunits, only NAKα3 is present in the presynaptic side of neurons (27,(46)(47)(48). Electrophysiological studies have also shown the importance of NAKα3 in the presynaptic function (49,50). Our data are consistent with ASPD binding to presynaptic NAKα3 of mature neurons, leading to activation of presynaptic N-type VGCC, and eventual death of NAKα3-expressing neurons.…”
Section: Discussionsupporting
confidence: 86%
“…This suggests an important role for this isozyme in mechanoreceptor function or signaling, perhaps by regulating high-frequency action potential patterning (Dobretsov et al, 2003;Yu et al, 2003;Mazzone and McGovern, 2006;. A recent study of auditory neurons suggests that the ␣ 3 containing isozyme may also be critical for their continuous, repetitive high-frequency activation (Kim et al, 2007). We have noted here and elsewhere the need for sustained high-frequency activation of the cough receptors when encoding coughs (Canning, 2007).…”
supporting
confidence: 57%
“…S2). Furthermore, in the brain, there are multiple Na,K-ATPase isoforms that each have cell-type-specific and developmentalspecific expression patterns (33,42) as well as different ouabain affinities (31,42). These spatial and temporal expression patterns of Na,K-ATPase isoform remain largely unknown but may be involved in the development and wiring of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…1A and 1B). The effect of ouabain on Na,K-ATPase varies in a dose-dependent manner (31,32); therefore, cortical neurons were exposed to graded concentrations of ouabain, and dendritic arbor growth was examined. As shown in Fig.…”
Section: Nak-atpase Receptor Activation Triggers Dendritic Growth Inmentioning
confidence: 99%
See 1 more Smart Citation